Traffic Characteristics for A Freeway Normal Section at Baghdad City - T. S. Al-Obaedi, Jalal; Al-temimy, Muhanad; Ali, Amal (International Journal of Engineering and Technology, 2018)
Traffic characteristics at highway sections are usually varying based on many factors including type of highways, geometric design and driversâ€™ behavior at a given area (country).Â This paper focuses on finding the characteristics for traffic on selected normal freeway section at Baghdad city.Â Video recordings and speed gun are used to collect data from a basic freeway section within Mohammed Al-Qassim freeway that represents the busiest freeway at the city.Â The estimated characteristics include the distribution of traffic among the available lanes, desired speed of traffic, lane-changing frequency, and headway distribution.Â For traffic distribution, it is found that traffic concentrates more in off side lane compared with other lanes for moderate to high flow rates.Â Regression models have been developed based on the available lane distribution data.Â The lane found to be increased with the increasing of traffic flow and the desired speeds found to be normally distributed.Â Examining the headway data shows that the shifted negative exponential distribution can be used to represent the headway distribution for low to intermediate traffic flow only.Â The findings of this work provides a good database for traffic characteristics for Iraqi highways as little effort has been given in previous research work.Â Â